Challenging parachute payments and unmasking English football's finances. Issue 1 (4th March 2022) - Wilson, Rob; Plumley, Daniel; Mondal, Sarthak; Parnell, Daniel
ABSTRACT: This commentary provides a rapid analysis of the impact of COVID-19 on English football's finances. The focus surrounds the distribution of wealth and financial disparity between clubs in the English football system leading to overspending and potential insolvency. We consider the impact of broadcast rights distribution, solidarity payments and parachute payments and provide strategic direction for a collective recovery. The intention is to stimulate discussion and analysis on how football governing bodies can use the COVID-19 pandemic to reset the finances of English football. Such discussion provides a more balanced, competitive suite of competitions that tackle financial inequality and put aside self-interest. We reposition the winner takes all narrative, requesting clubs to reflect on the sporting product that has led to both success and failure at an individual club level.